IMPLEMENTASI DATA MINING SEBAGAI SISTEM REKOMENDASI KONSUMEN DALAM PEMILIHAN SMARTPHONE - Dedi Gunawan, Angga Endra Wibisono (STMIK Sinar Nusantara, 2016)
Data mining is a process of extracting useful information from database which can help data owner to make decision. Data mining can be implemented in many areas spans from scientifict aspect to business area. In this research one of the data mining techniques that is called multiple linear regression is implemented as a recommender system to give a recommendation for custumer in order to choose a suitable smartphone. Linier regression is an modelling approach to predict a relationship between dependent variabel Y and independent variable X. Dependent variable Y is a type and serie of a smartphone while customers age, income per month, smartphone price, rear camera, front camera, number of phone card and memory capacity are the free variables X1, X2, X3, X4, X5, X6, X7 respectively. The result of this research is a web-based recommender system that runs variables input from user into several recommended product. Based on the testing result there are no error found upon the system. Furthermore, accuration testing shows that the system is able to give good recommendation for customer with error value between 0.2 and 0.5.Keywords: Data mining, multiple linear regression, recomender system